Medical Students Preference in Blended Learning after Covid-19 Pandemic: Online vs Offline - Widyandana, Widyandana; Izzah, Nurul; Utomo, Prattama Santoso; Claramita, Mora (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2024)
Background: Blended learning has been preferred to be implicated during the transition phase after the pandemic. Nowadays, universities started to shift back into offline learning after being retained for nearly 2 years. The effectiveness of digital learning should be considered. Even though it provided simplicity and ease, the effectiveness was questionable due to a lack of interaction and hands-on practice. Thus, blended learning combines face-to-face and digital learning to maximise the knowledge transfer during classes. However, the efficacy of both offline and online learning was still questioned. Each has benefits and drawbacks, which differ for every student in various conditions. This study assessed medical students’ preferences in the blended learning era.Method: This study used a cross-sectional design. An online survey was conducted among first-year medical students in the Faculty of Medicine, Public Health, and Nursing Universitas Gadjah Mada (N=201). Data were analysed using a descriptive qualitative approach referring to Doyle et al. Results: Among 201 students who were included in our study, the topmost learning categories chosen to be given in an online setting were lectures (N=97), learning skills (N=18), and discussion (N=16).  For offline settings, they preferred practical skills (N=114), lectures (N=41), and skills laboratory (N=40). Students mentioned network problems as their finest challenge during online classes, and network support was the most needed to improve the learning outcome.  Conclusion: Passive activities that require the least effort were favoured to be given online, and activities requiring active participation were preferred to be given face-to-face. Limitations were challenging for students in participating in online classes; further evaluation and improvement are needed.